Gaulish SUIOREBE ‘with two sisters’ - Witczak, Krzysztof Tomasz (Lingua Posnaniensis, 2015)
Traces of the dual number may be identified in the Gaulish language on the basis of the historical-comparative method. It is suggested that the Gaulish form SUIOREBE represents an instrumental dual with the sociative meaning ‘with two sisters’. The conclusion is that the Gaulish SUIOREBE contains the dual base SUIORE- (< IE. *swesore ‘two sisters’) accompanied by the dual ending -BE (< IE. *-bhēm).